Impacts of Climate Change on Biodiversity and Ecosystem Services: Direction for Future Research - Bhattarai, Utsab (Hydro Nepal: Journal of Water, Energy and Environment, 2017)
The potential adverse effects of climate change have posed serious threat to all species of the planet in many ways. Species’ functional characteristics strongly influence ecosystem properties. Although significant numbers of studies have already explored the interrelationship between biodiversity, ecosystem services and climate change more focused studies have now begun to appear with the goal of investigating and analyzing the negative consequences of climate change on life support systems. This review paper discusses the impacts of climate change on biodiversity and redirects how these losses of biological species on earth have affected and will continue to have effects on the delivery chain of ecosystem services. Concluding section of this paper spotlights on possible mitigation and adaptation plan of actions which contributes in minimizing climate change induced risks while supporting biodiversity and thus the entire ecosystem services. The timeliness of this review is evident because the concerns regarding the potential impacts of global climate change on species and ecosystem services are widely and seriously recognized as major threat of our time. HYDRO Nepal Journal Journal of Water Energy and Environment Issue: 20 Page: 41-48